A Feasibility study on establishing a biomedical waste treatment facility in Davao - Abalos, Maria Lourdes L.; Baredas, Jennifer R.; Esguera, Kathryn L. (aDiliman, Quezon City College of Engineering, 2004)
Hospitals deals with various illnesses, diseases, and injuries and in the process generate infectious wastes. These wastes may contain infectious agents, sharps, hazardous chemicals, and pathogens. Disposal of these wastes without treatment poses a threat of spreading diseases. With the absence of a biomedical waste treatment facility in Mindanao, hospitals do not have any alternative but t bury their infectious wastes within the hospital premises or worse dispose them without treatment together with other municipal wastes. However, the practice of deep burial and dumping in controlled dump sites will be prohibited by March 1, 2006. Two important pieces of legislation have been passed in the last few years, which concerns health care wastes. The first is the Toxic and Hazardous Substances and Nuclear Waste Control Act of 1990 (Republic Act 6969), which requires waste generators to ensure that its hazardous or biomedical waste is properly collected, transported, treated, and disposed. The second is the Clean Air Act (Republic Act 8749), which prohibits the use of incinerators for treating wastes effective July 17, 2003. With the implementation of these government regulations, the need for alternative means of disposing infectious biomedical wast arises. Taking all these issues and concerns into consideration, a feasibility study was conducted to investigate the viability of establishing a biomedical treatment facility in Mindanao. Through the application of non-incineration technology, JKL Treaters, Inc. aims to eliminate the threat of environmental pollution. The company's greatest concern is to treat the biomedical wastes properly before disposal in order to prevent these infectious wastes from spreading diseases or causing injury. JKL Treaters, Inc. will be the pioneer biomedical waste treatment facility in Mindanao. The company will provide a complete package of collection, transportation, treatment and disposal of infectious wastes from hospitals. With accreditation from the Environmental Management Bureau, availing the services offered by the company will ensure the hospitals that their infectious wastes will not be a threat anymore to the health of the general public. The first step in determining the success of the service is to conduct a market feasibility study. Based on primary and secondary data, including the relevant information on the competitors and the market area, it was determined that the treatment facility will be best established in the Mindanao Region, more specifically, in the province of Davao. The estimated amount of infectious waste that will be generated by the region in the year 2005 was determined to be 659,667.00 kilograms. This value also approximates the potential demand for the service. Based on the survey conducted on various hospitals in Mindanano, primary,secondary and tertiary hospitals, both government- and privately-owned are willing to avail of the service. Furthermore, with the results of the survey and the estimated market growth, the market share for the next five years was determined. After establishing the commercial feasibility of the service, it was necessary to determine its technological feasibility given the existing technical constraints and government regulations. Based on the research and evaluation, the treatment facility will employ High-Heat treatment technology, more specifically, Thermal Oxidation for its treatment process. Since there are no local manufacturers of on incineration technologies, the machine to be utilized will be imported. Other equipment and supplies such as material handling equipment and consumables are locally available. The facility will b located in Bgy. Licanan, Davao City, a heavy industrial zone and will require 8,000 square feet of lot area for the plant. The treatment machine will be leased, with payments every quarter. Based on the technical feasibility study, it was estimated that the project would incur a cost of Php 21,930,687. From this amount Php 11,816,543 will be required as a start-up capital in order to cover the initial investment expenditure for and operating expenses for the first year of operation. To finance the project, a combined debt and equity financing scheme will be implemented in order to raise the needed capital. The company will use its fixed investments as collateral for debt financing. Since the company will be registered as a corporation, the remaining capital requirement will be financed through equity by releasing 16,512,141.00 shares of stock with a par value of Php 1.00. Based on the pro forma financial statements, the company will realize an approximate net profit of Php 39,987,810.00 for the first five years of operation. Financial ratios and other measures of performance were computed and compared with industry competitors. The values showed that the company could be at par with other companies of similar industry. The Internal Rate of Return (IRR) was computed to be 43.95% , which is higher than the standard MARR (30%) The project will also have a Net Present Value (NPV ) of Php 5,252,804. With an IRR greater than the MARR and a positive NPV, the project proves to be a good investment. Results of the social probability study further established the attractiveness of the project by showing that the benefits significantly outweighs the costs to the society. The Benefit-Cost Ratio is equal to 3.4. Based on all the findings from the market, technical, financial, and social profitability phases of the study, it was determined that the establishment of a biomedical treatment facility in Mindanao is feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: JKL Treaters, Inc; Hazardous waste; Participatory monitoring and evaluation (Project management)